Delivery of Impacted Fetal Head at Caesarean Section - Surgical Technique - Ghosh, T.S.; Kwawukume, E.Y. (Ghana Medical Journal, 1992)
A type of U-shaped incision with a broad base to deliver the impacted fetal head or the neglected shoulder at cesarean Section is presented. This incision combined with an assistant dislodging the wedged fetal head upwards before incising the lower segment of the uterus prevented lateral extension into the uterine arteries in 56 patients at the Korle Bu Teaching Hospital. The surgical technique is described.
Journal Article on Delivery of Impacted Fetal Head
Keywords: Impacted fetal head; Caesarean section; Surgical technique